Comparison of Positive Deviance between Normal Nutrition and Undernutrition in Children Under Five Years Old from Low-Income Families at Community Health Centres in Medan - Nasution, Ramadhani Syafitri; Mat, Khairi Che; Mohamad, Marhazlina (International Journal of Public Health Excellence (IJPHE), 2024)
Positive deviance in low-income families is a mechanism by which individuals or groups continue to thrive or meet standards despite facing challenging conditions. One of the goals of positive deviance is to prevent child malnutrition by changing community habits about feeding, caring, hygiene, and health seeking practices. Malnutrition early in life will affect the growth and development of children and the quality of life thereafter. The study aims to compare the positive deviances between children with normal nutrition and undernutrition. This cross-sectional study was conducted in 39 public health centres in Medan, West Indonesia, where a total of 80 children (40 with normal nutrition and 40 with undernutrition) were recruited using purposive sampling. Nutritional status (normal or undernutrition) was determined using body mass index-for-age (BMI-for-age) z-scores, according to WHO reference values. Positive deviance behaviours were assessed using a validated questionnaire, and anthropometric parameters such as weight, height, BMI, and triceps skinfold were measured. Haemoglobin levels were taken as a biological measurement of the condition. The Mann-Whitney test demonstrated that the positive deviance practices of feeding, caring, hygiene, and health-seeking behaviours were significantly better among normal nourished children than undernourished children (p<0.05). Children from families with positive deviance practices have better nutritional status despite living in economically limited conditions. This indicates that family behaviours and practices can play a crucial role in enhancing children's nutritional and health status, regardless of financial or environmental constraints. Integrating positive deviance approaches alongside additional interventions could be effective in improving children's nutritional status.